The Role of Echocardiography in Heart Failure with Preserved Ejection Fraction: What Do We Want from Imaging? - Obokata, Masaru (Heart Fail Clin, 2019)
Non-invasive imaging, particularly echocardiography, plays a central role in the evaluation for heart failure with preserved ejection fraction (HFpEF). Echocardiography helps to rule in HFpEF among patients with unexplained dyspnea when the diagnosis is uncertain. In established HFpEF, echocardiography provides important insights into pathophysiology and phenotyping, such as isolated left ventricular diastolic dysfunction, left atrial dysfunction, abnormal right ventricular- pulmonary artery coupling, ischemia, or obesity phenotypes. Finally, imaging enables risk stratification for HFpEF. In this review, we will provide a critical appraisal of the role of echocardiography in the diagnosis and evaluation of HFpEF.